GAMBARAN KADAR GLUKOSA DARAH DAN TEKANAN DARAH PENDERITA DIABETES MELITUS PESERTA PROLANIS DI KLINIK ROMANA TANJUNG ANOM MEDAN TAHUN 2024 - Indra Hizkia Perangin-angin; Jagentar Parlindungan Pane; Ririn Verawaty Sirait (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Diabetes mellitus is one of the diseases that causes death which ranks seventh in the world and the third deadly disease in Indonesia. Improper management of patients with diabetes mellitus can lead to several complications or further consequences that are dangerous for sufferers. Increased blood glucose levels over time can cause serious damage to the heart, blood vessels, eyes, kidneys, and nerves. This study aims to identify blood glucose levels and blood pressure of patients with diabetes mellitus prolanis participants. The research design is descriptive with a cross sectional approach. The sampling technique used accidental sampling with the number of respondents with DM prolanis participants as many as 55 people. The instrument used was an observation sheet with measuring instruments Glucometer Auto check and digital tension meter. The results obtained are normal blood glucose levels (fasting) as many as 34 respondents (61.8%) and 21 respondents (38.2%) with abnormal, with normal blood pressure levels as many as 25 respondents (45.5%), as many as 16 respondents (29.1%) Pre-hypertension, and 14 respondents (25.5%) with grade 1 Hypertension. The conclusion of the study is that there are 34 respondents with normal blood glucose levels and 25 respondents with normal blood pressure levels. It is recommended that prolanis participants continue to actively participate in activities and regularly follow medication.